Random Time Delay Mitigation in Pulse Radar Systems Implementation using Universal Software Radio Peripheral (USRP) and GNU Radio Companion (GRC) - Alifia Fitri Utami; Iswandi Iswandi; I Wayan Mustika (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
Abstract— Radar or radio detection and ranging has a basic function to detect and measure a target range. One of the latest developments is Software Defined Radio (SDR)-based radar. An example of SDR implementation is by using Universal Software Radio Peripheral (USRP) as hardware and GNU Radio Companion (GRC) as software. The simplest radar type is pulse radar in which system timing is crucial. Meanwhile, in pulse radar system implementation using USRP and GRC, there is an issue with the random processing time delay between communication protocol of USRP and computer running the GRC, which causes incorrect measurement. This research aims to analyze the random time delay in the pulse radar system implementation by using USRP and GRC to anticipate the effect of random time delay. Pulse radar systems implementation is administered by transmitting 128 bits of Barker code and performing correlation between transmitted and received radar signal. Research result shows that the random time delay can be anticipated by making the direct reception from radar transmitter to receiver as the reference in range calculation.